Pyrrole-embedded [60]fullerenes - Reuther, Uwe; Hirsch, Andreas (Chemical Communications, 1998)
The treatment of the monoarylated azafullerenes ArCN with iodine monochloride in carbon disulfide leads to the exclusive formation of the tetrachlorinated heterofullerenes ClArCN which contain a pyrrole moiety in the fullerene cag